HUNIAN WARGA YANG ‘KOMPAK DAN BERKELANJUTAN’ DI KAMPUNG SAWAH, JAKARTA UTARA - Erika Visca Lina (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
Urban sprawl due to limited land for living causes more residential development on the edge of the city. Land fragmentation results in the need for high mobility. With the characteristics of settlements in urban sprawl areas that use large land and large house areas, the demand for water and energy, especially electricity, increases. Due to the lack of clear arrangements and regulations from the central government, residents who refuse to live far from their place of work choose to live in the urban village area. Due to the shortage of residential land, inadequate settlements began to appear in urban areas, which are often called Kampung Kota. Even though it is located in an urban area, Kampung Kota is still a village with difficult access, poor population, and is a form of adaptation to the lack of residential land. The organically formed Kampung Kota is a reflection of the vital needs of the city dwellers, namely accessibility and a comfortable living environment. The solution to the problem of urban sprawl can be overcome with the compact city principle, which has been reflected in Kampung Kota which was originally organic. Compact city is an urban planning that focuses on densely populated mixed-use functions. This concept is based on the use of efficient public transportation and has an urban setting that encourages residents to walk or cycle, lower energy consumption, and reduce pollution. Therefore, the expansion of Kampung Kota with compact city principles that are similar to each other can be applied also is expected to become a prototype for compact Kampung Kota housing. Keywords: compact city; kampung sawah; urban sprawl; urban village Abstrak Perkembangan kota ditandai dengan urban sprawl, karena terbatasnya lahan tinggal menyebabkan pembangunan hunian di pinggir kota. Fragmentasi lahan akibat urban sprawl mengakibatkan diperlukannya mobilitas tinggi. Dengan karakteristik permukiman di daerah urban sprawl yang menggunakan lahan besar dan luasan rumah yang besar juga membuat kebutuhan air dan energi terutama listrik meningkat. Karena kurangnya penataan dan regulasi yang jelas dari pemerintah pusat, penduduk yang menolak tinggal jauh dari tempat bekerja memilih untuk tinggal di area kampung kota. Akibat kekurangan lahan permukiman, mulai bermunculan permukiman tidak layak di area perkotaan, yang sering disebut kampung kota. Meskipun letaknya di perkotaan, kampung kota masih bersifat kampung yang  sulit diakses, masalah kemiskinan penduduk, dan merupakan adaptasi penduduk akan kurangnya lahan tinggal. Kampung Kota yang terbentuk secara organik merupakan cermin kebutuhan vital penduduk kota, yakni aksesibilitas dan lingkungan hidup yang nyaman.  Solusi untuk permasalahan urban sprawl dapat diatasi dengan prinsip compact city, yang telah tercermin dalam Kampung Kota. Compact city adalah sebuah perencanaan urban yang berfokus pada fungsi mixed-use padat penduduk. Konsep ini memiliki dasaran penggunaan transportasi publik yang efisien dan memiliki tatanan urban yang mendorong penduduknya untuk berjalan kaki atau bersepeda, konsumsi energi yang rendah, dan mengurangi polusi. Oleh karena itu perluasan kampung kota dengan prinsip compact city yang similar satu sama lain dapat diterapkan. Prinsip compact city yang telah tercermin dalam kampung kota di Kampung Sawah diharapkan dapat menjadi prototype hunian kompak kampung kota.